2022
DOI: 10.3390/mi13071078
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Characterization of Optimized Dual-Frequency Vibration Energy Harvesters for Low-Power Industrial Applications

Abstract: We present a multiresonant vibration energy harvester designed for ultra-low-power applications in industrial environments together with an optimized harvester design. The proposed device features dual-frequency operation, enabling the harvesting of energy over a wider operational frequency range. It has been designed such that its harvesting bandwidth range is [50, 100] Hz, which is a typical frequency range for vibrations found in industrial applications. At an excitation level of 0.5 g, a maximum mean power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…In our case, we focus on serial designs, i.e., cascading simple beam PEHs instead of arranging them into an array [ 13 ]. In [ 14 ], we showed that cascading/serial designs significantly outperform array configurations and confirmed previously presented results from, e.g., [ 15 , 16 ].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our case, we focus on serial designs, i.e., cascading simple beam PEHs instead of arranging them into an array [ 13 ]. In [ 14 ], we showed that cascading/serial designs significantly outperform array configurations and confirmed previously presented results from, e.g., [ 15 , 16 ].…”
Section: Introductionsupporting
confidence: 86%
“…In [ 20 ], stack PEH for automotive is optimized, with regard to parameters, such as the number of stack layers or height to cross-section ratio. For the folded-beam PEH, we implemented a two-stage global parametric design optimization and proposed novel geometries in [ 14 , 21 , 22 ]. Parameter optimizations, however, are strongly limited, as the topology of the final design is already determined by the initial design.…”
Section: Introductionmentioning
confidence: 99%
“…Since the sensor node device is designed to rely exclusively on the output of the vibration-based energy harvester, it is imperative to estimate the available power budget. This estimation will guide our choice of a suitable microcontroller platform, as discussed in [ 38 ]. In the latter, we conducted a comprehensive experimental characterization of various energy harvester designs depicted in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In our previous works [ 34 , 35 , 36 ], we introduced an innovative vibration-based energy harvester design and investigated various methods to enhance the system’s frequency adaptability and broaden its harvesting bandwidth. Furthermore, in a subsequent study [ 37 , 38 ], we presented optimized iterations of our harvester design and conducted experimental demonstrations that showcased enhanced performances.…”
Section: Introductionmentioning
confidence: 99%
“…However, the systems considered in these works require precision parameter tuning, which is not always feasible in real technical systems. In particular, much attention has been paid to the values of electric voltage [ 15 ], temperature conditions [ 16 ], and noise exposure [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%